Regional Cerebral Blood Flow in Mania: Assessment Using 320-Slice Computed Tomography - Wang, Yiming; Liu, Xingde; Li, Peifan; Zhou, Haiyan; Yang, Lixia; Zheng, Lei; Xie, Pingxia; Li, Lingjiang; Liao, D. Joshua; Liu, Qianqian; Fang, Deyu (Frontiers in Psychiatry, 2018)
Objectives: While evidence that episodes of mania in bipolar I are associated with changes in bioenergetic and regional cerebral blood flow (rCBF) and cerebral blood flow velocity (rCBFV), both the regions and the extent of these changes have not yet been defined. Therefore, we determined the pattern of regional cerebral perfusion mania patients and using patients with major depressive disorder (MDD) as positive controls and healthy participants as negative controls. Methods: Twenty participants with mania, together with 22 MDD patients and 24 healthy volunteers, were recruited for this study. On all participants, Transcranial Doppler (TCD) was conducted to measure rCBFV parameters, 320-slice CT was conducted to measure rCBF in the different cerebral artery regions, and hematological parameters were assessed. ANOVA and Pearson's tests were used for the statistical analysis. Results: Our data indicated that rCBF in the medial temporal lobe and hippocampus, especially in the left medial temporal lobe and the right hippocampus, was increased in the mania group compared with the control and MDD groups (p < 0.01). In contrast, rCBF in the medial temporal lobe and hippocampus was decreased in the depression group (p < 0.01) compared with healthy controls. In addition, values of rCBFV in the bilateral internal carotid arteries (ICAs) and middle cerebral arteries (MCA) were increased in mania (p < 0.01) in comparison to the MDD group. Whole blood viscosity and hematocrit as well as red blood cell sedimentation rate remained unchanged in all group (p > 0.05). Conclusions: In mania, rCBF is increased in the medial temporal lobe and hippocampus, with a corresponding increase in rCBFV in the same regions.